Effect of nanocellulose with ethylene glycol for automotive radiator application - I., Naiman; Ramasamy, D.; Kadirgama, Kumaran (IOP Publishing, 2020)
One of the effort to increase the effectiveness of radiator is by adding nanocellulose in radiator coolant. Furthermore, the percentage of nanocelluose plays an important role to make sure that the amount of heat transfer can be increased by increasing the percentage of nanopcellulose. The nanocelluose is used in this experiment as the nanoparticles In addition, Nanofluids are suspensions of nanoparticles in base fluids, a new challenge for thermal sciences provided by nanotechnology. Nanofluids have unique features different from conventional solid-liquid mixtures in which mm or m sized particles of metals and non-metals are dispersed. Due to their excellent characteristics, nanofluids find wide applications in enhancing heat transfer. Radiator was modelled using One-Dimensional simulation software to predict the performance characteristics and effectiveness of the radiator with addition of nanoparticles. Besides that, method of using micro channels and fins to extend the cooling rate of a radiator ended up being a traditional technology which already reached to its maximum limit. Moreover, heat transfer coefficient of cellulose nanofluids can be increased by increasing the size of the radiator. Increase in size of radiator may enhance better and help to increase the rate of heat transfer. In addition, it clearly states that when the flow rate of the coolant or working fluid in the radiator cooling system increase the rate of heat transfer also is increases.